CONTRACTS FOR THE FIFTH LICENSING ROUND AND THE LOCATION OF NATURAL GAS IN IRAQ (World Economics and Finance Bulletin, 2023)
After the year 2033, Iraq entered the field of oil investment, which is an important turning point in the history of Iraq after isolation and wars. International companies in the field of investing in this important sector and in order to promote production capacities, as well as the development of oil fields, and because of the increasing debt burden on Iraq, and this restructuring requires huge financial and technical capabilities, prompting the government to adopt a service method for developing oil fields by offering a number of Licensing rounds, which are meant to be contracts for the rehabilitation and development of explored and produced oil fields for a specified period of up to seven years, and the most important of these investments: the first and second rounds in 2009-2010, where these two rounds focused on developing the oil fields of the south, the aim of the first round, which was announced On 30/6/2008 and it continued for a year, the oil production rates increased (1.5) million barrels per day, by 10%, within three years, to reach after seven years to 3.750 million barrels per day, and until it reaches that level. In 2017, it amounted to 5 million barrels per day. The first licensing round focused on increasing oil production rates, with the aim of increasing its profits. It did not attach importance to the investment of associated gas, which resulted in the loss of the material value of this gas.
Keywords: oil field; International companies